Efek Pemanasan Bertingkat terhadap Kandungan Antioksidan Minyak Sawit Merah dan Minyak Goreng dalam Proses Deep Fat Frying - Saragih , Diego Pranata; Siahaan , Jessica Patresia; Siahaan, Andreas Kevin; Nur Ariyani Agustina (Jurnal Agro Fabrica, 2025)
Each cooking oil has differences, especially in the content of antioxidant compounds. Oil with high antioxidant content can reduce oil damage during the process of use. The content of antioxidant compounds in red palm oil and cooking oil can cause oil damage in red palm oil and cooking oil also varies. The study aims to determine the effect of oil type on antioxidant levels in red palm oil with the deep fat frying method and to determine the difference in temperature affecting antioxidant levels in cooking oil with the deep fat frying method. This study was conducted using the Completely Randomized Design method in factorial form, with 2 treatment factors. The first treatment is the type of oil (M) consisting of M1 = red palm oil (RPO) and M2 = palm cooking oil (PO). The second factor is the variation of frying temperature with the deep fat frying method with 4 levels, namely: S1 = without frying (control), S2 = 180 ° C, S3 = 230 ° C and S4 = 280 ° C. Data analysis was carried out descriptively. The results of the study showed that red palm oil has a higher antioxidant content compared to palm oil and cooking oil with the deep fat frying method. Red palm oil has a DPPH percentage of 28.01%, while palm cooking oil has a DPPH percentage of 28.90. The lower the DPPH percentage, the higher the antioxidant content. The antioxidant content of red palm oil and cooking oil with the deep fat frying method differs with increasing frying temperature. Red palm oil experiences a decrease in antioxidant content with increasing frying temperature, while palm cooking oil experiences an increase in antioxidant content with increasing frying temperature.